2009
DOI: 10.1097/mej.0b013e3283036e47
|View full text |Cite
|
Sign up to set email alerts
|

Handling of drug-related emergencies: an evaluation of emergency medical dispatch

Abstract: On the basis of the interviews and the survey, cases were handled according to guidelines. The log recordings, however, disclosed deviation from the protocol. Alcohol intoxication was associated with higher rate of deviation from the protocol compared with other intoxications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Our result of approximately 75% use of Index lies between the divergent findings from the 2005 study, with 99% self-reported Index guideline adherence and 64% adherence based on log-recordings [11]. To our knowledge there are no other studies addressing adherence to criteria based guidelines.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our result of approximately 75% use of Index lies between the divergent findings from the 2005 study, with 99% self-reported Index guideline adherence and 64% adherence based on log-recordings [11]. To our knowledge there are no other studies addressing adherence to criteria based guidelines.…”
Section: Discussionmentioning
confidence: 68%
“…A recent systematic review on adherence to guidelines and protocols in the pre-hospital setting was not able to identify any eligible study in the emergency medical dispatch setting, neither CBD nor MPDS based [10]. However, a Norwegian study from 2005 evaluated dispatch in drug-related emergencies, and found an Index adherence of 99% based on multiple choice questionnaire, but only 64% guideline adherence based on log recordings [11]. …”
Section: Introductionmentioning
confidence: 99%
“…This result is congruent with the study of Bång et al where the EMD asked only 41 percent of the callers if the patient was breathing normally [ 11 ]. Previous studies describe protocol compliance as an important factor for successfully triaging in the EMCC [ 3 , 6 ]. In our study, there were some cases where although the RN followed the assessment protocol and ascertained whether the patient was breathing and/or conscious, nevertheless, the RN did not treat the call as a high priority case.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of the patient’s symptoms result in a better outcome for out- of-hospital cardiac arrest patients [ 3 ], and theoretically early identification may be important in other medical emergencies such as myocardial infarction [ 4 ] or stroke [ 5 ]. Previous studies have described the complexity of assessing an emergency call [ 3 , 6 , 7 ]. There are also studies identifying possible reasons for not identifying the caller’s need of care; language barriers [ 8 - 10 ] unnecessary questions asked by the EMD during the call [ 11 ], and lack of information from the caller [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of such standardized protocols for the assessment of the patient's health status is reported to increase the detection of health impairments by emergency medical dispatchers and thus to improve the treatment [30][31][32]. Furthermore, the dispatchers should have suitable opportunities for coping with their emotions and exchanging their feelings and impressions at regular intervals to reduce their observed chronic stress level.…”
Section: Discussionmentioning
confidence: 99%